Dampak alih fungsi hutan mangrove terhadap ekonomi masyarakat di Telaga Wasti Sowi IV Manokwari Papua Barat - Yohan F. Rumwaropen; Bambang Nugroho; Anton Sineri (Cassowary, 2019)
Mangrove forest is a vegetation that grows in the estuary beaches and who has the function of ecological, biological, economic and social culture, but now its existence has been degraded by the use of a less appropriate or changing function. Research on the structure of mangrove forest vegetation in the Wasti Bay Sowi IV Manokwari District of Southern District Manokwari conducted in April 2018 with the aim to determine the structure of mangrove forest vegetation and utilization. The method used in this research is the approach of ecological (biological) and anthropological approach. From the analysis of vegetation, found as many as 8 species of mangrove plants. Rhizophora apiculata is the dominant species on the level of a tree with a Density Value of 784.66 Individuals/Ha with an Important Value Index (IVI) 50.06 followed Rhizophora mucronata with a Density Value of 770.34 Individuals/Ha with the Important Value Index (IVI) 41.01. At the level of belta Rhizophora mucronata is the dominant species with a Density Value of 385.66 Individuals/Ha with the Important Value Index (IVI) 45.13 then Rhizophora apiculata with a Density Value of 263.33 Individuals/Ha with the Important Value Index (IVI) 40.22. At the seedling stage Rhizophora mucronata a dominant species with a Density Value of 760.00 Individuals/Ha with the Important Value Index (IVI) 45.42 and Rhizophora apiculata had Density Value of 681.66 Individuals/Ha with the Important Value Index (IVI) 41.04. Based on interviews of 8 mangrove species found in the observation plot, 3 species used as building material, 6 species as a source of firewood, 3 species as drugs and 5 species for other purposes.